2014
DOI: 10.1039/c4nr01234h
|View full text |Cite
|
Sign up to set email alerts
|

A general mechanism for intracellular toxicity of metal-containing nanoparticles

Abstract: We demonstrate a general mechanism for the toxicity induced by metal-containing NPs, named “lysosome-enhanced Trojan horse effect”, which provides design rules to engineer safer NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
294
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(314 citation statements)
references
References 61 publications
(103 reference statements)
18
294
1
1
Order By: Relevance
“…Notably, the cytotoxicity of metallic NPs is frequently associated with leaching metal ions (Sabella et al 2014;Zook et al 2012;Setua et al 2014). Rotoli et al (2012) found that an increase in the permeability of a monolayer of Calu2 cells exposed to CuO, CeO 2 or TiO 2 NPs correlated with a decrease in metabolic activity on the seventh day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the cytotoxicity of metallic NPs is frequently associated with leaching metal ions (Sabella et al 2014;Zook et al 2012;Setua et al 2014). Rotoli et al (2012) found that an increase in the permeability of a monolayer of Calu2 cells exposed to CuO, CeO 2 or TiO 2 NPs correlated with a decrease in metabolic activity on the seventh day.…”
Section: Resultsmentioning
confidence: 99%
“…It has been discussed that there could be a linear correlation between short and long-term toxicity (Scheers et al 2001). However, the possibility of exceptions due to various reasons, especially concerning NPs where the particles are covered with biocorona in physiological conditions, has been mentioned earlier (Sabella et al 2014). The need to collect cytotoxicity data over time is derived also from the guidelines of the NICEATM summary of the multicenter evaluation of in vitro cytotoxicity (MEIC) (NICEATM 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed sporozoite/shell ratio decreases at much lower AgNP concentrations than those of silver ions (statistically significant effects noted at 5 g/ml versus 500 g/ml). One explanation is that the presence of AgNPs contributes to greater silver internalization, potentially mediated by the local low pH enhancing silver release following AgNP binding to the membrane, in an enhanced "Trojan horse" effect which has previously been suggested as a mechanism for nanoparticle toxicology after uptake into lysosomes (29). An alternative is that bound AgNPs are not removed before the excystation assay and thus remain a source of silver ions as sporozoites are excysted, although the results of Su et al suggest the occurrence of sporozoite destruction before the oocyst wall is broken.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies could neglect the role of ROS. Thus, it can be stated that ROS production may not be the sole player of DNA damage and some other mechanism may also be responsible for its toxicity like leaching of Au ions from nanoparticles and complexing effect with surrounding biomacromolecules (65,73). Antioxidants have the ability to destroy the ROS and a large number of antioxidants have been reported which have been extensively used in the clinical practice.…”
Section: Special Case: Oxidation Stressmentioning
confidence: 99%